2017
DOI: 10.1002/jbm.a.36067
|View full text |Cite
|
Sign up to set email alerts
|

Thermogelling chitosan lactate hydrogel improves functional recovery after a C2 spinal cord hemisection in rat

Abstract: The present study was designed to provide an appropriate micro-environment for regenerating axotomized neurons and proliferating/migrating cells. Because of its intrinsic permissive properties, biocompatibility and biodegradability, we chose to evaluate the therapeutic effectiveness of a chitosan-based biopolymer. The biomaterial toxicity was measured through in vitro test based on fibroblast cell survival on thermogelling chitosan lactate hydrogel substrate and then polymer was implanted into a C2 hemisection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 110 publications
1
24
0
Order By: Relevance
“…On the other hand, in situ gelling can be achieved by physical interactions, providing the advantages of cell delivery without previous geometrical shape preparation of hydrogels and with a less invasive implantation process (Shariatinia and Jalali, 2018). For application in the CNS, hydrogels have been obtained from chitosan (Chedly et al, 2017), its derivatives as CMC (Xu et al, 2018) and chitosan lactate (Nawrotek et al, 2017), and mixtures with other polymers like gelatin (Gao S. et al, 2014). Biodegradable scaffolds are mainly structured by freeze-drying but can be also obtained by electrospinning, solvent evaporation, supercritical carbon dioxide, and 3D printing (Croisier and Jérôme, 2013;Wang Y. et al, 2018;Sun et al, 2019).…”
Section: Chitosan-based Materials For Tissue Engineering and Regeneramentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in situ gelling can be achieved by physical interactions, providing the advantages of cell delivery without previous geometrical shape preparation of hydrogels and with a less invasive implantation process (Shariatinia and Jalali, 2018). For application in the CNS, hydrogels have been obtained from chitosan (Chedly et al, 2017), its derivatives as CMC (Xu et al, 2018) and chitosan lactate (Nawrotek et al, 2017), and mixtures with other polymers like gelatin (Gao S. et al, 2014). Biodegradable scaffolds are mainly structured by freeze-drying but can be also obtained by electrospinning, solvent evaporation, supercritical carbon dioxide, and 3D printing (Croisier and Jérôme, 2013;Wang Y. et al, 2018;Sun et al, 2019).…”
Section: Chitosan-based Materials For Tissue Engineering and Regeneramentioning
confidence: 99%
“…Chitosan hydrogels have proved to provide a suitable micro-environment for axons regrowth and increase the survival rate of damaged neurons in different animal models. These hydrogels have shown remarkable potential in CNS repair, even in the absence of added trophic factors or without a detailed design of its structure (Tseng et al, 2015;Nawrotek et al, 2017). Chedly et al (2017) elaborated a fragmented physical hydrogel suspension employing unmodified chitosan for its implantation in rat SCI (immediately after the injury).…”
Section: Chitosan-based Scaffoldingmentioning
confidence: 99%
“…Thermo‐sensitive hydrogels could achieve transformation between liquid and hydrogels according to the actual environmental temperature and act as a drug reservoir in injection site, with the advantages of controlled release, targeted drug delivery, and low toxicity (Culver, Clegg, & Peppas, 2017; Ganji, Abdekhodaie, & Ramazani, 2007; Hamedi, Moradi, Hudson, & Tonelli, 2018; Jayakumar, Prabaharan, Sudheesh Kumar, Nair, & Tamura, 2011; Klouda & Mikos, 2008; McKenzie et al, 2015). Therefore, thermo‐sensitive hydrogels are widely used for mucosal drug delivery in situ, such as nasal drug delivery, ophthalmic drug delivery, percutaneous drug delivery, and vaginal drug delivery (Cao, Yan, Hu, & Zhou, 2015; Cheng et al, 2016; Fabiano, Bizzarri, & Zambito, 2017; Jeong, Kim, & Bae, 2012; Kim et al, 2010; Lisková et al, 2015; Nawrotek et al, 2017; Ressler et al, 2018; Ruan, Yu, Guo, Jiang, & Luo, 2018; Tsai et al, 2016). This type of administration effectively avoids the hepatic first‐pass effect and gastrointestinal degradation of oral drugs, reduces the systemic toxicity of drugs during tumor chemotherapy, and greatly improves the bioavailability of drugs, which shows strong development value and application potential (Abbas, Refai, & Sayed, 2018; Azadi, Hassanjili, & Zarrabi, 2018; Huang, Feng, Yu, & Li, 2011; Jiang, Meng, Wu, & Qi, 2016; Moawad, Ali, & Salem, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CS exhibits in vitro neuroprotective effects on several neuronal cell lines, by exerting anti-inflammatory activities and protecting from apoptotic mechanisms [29]. More recent studies focused on the development of CS porous matrices, solutions, and hydrogels, have revealed that CS scaffolds-when implanted at the site of SCI in the sub-acute stage-provide a protective and neurotrophic microenvironment that is functional both to the survival of damaged endogenous neurons and to the differentiation of transplanted stem cells into neuronal ones [28,[30][31][32]. ALG is an anionic polysaccharide, generally extracted from brown algae (Phaeophyceae species).…”
Section: Introductionmentioning
confidence: 99%